IMPACT OF FOOD PREFERENCES ON THE DEVELOPMENT OF PATHOLOGICAL CHANGES IN THE MASTICATORY APPARATUS IN YOUNG PATIENTS - Desislava Konstantinova; Mariana Dimova; Darina Naydenova (Peytchinski Publishing, 2016)
Food can have a mighty biological, therapeutic and preventive effect, yet its breakdown can provide the perfect setting for tooth decay and its implications, diseases of the periodontium and the oral mucosa. Due to the high incidence of periodontal and hard dental tissues pathologies among adolescents they have been ranked as socially significant diseases. A damaged dental-jaw apparatus may lead to forming unhealthy eating habits, more sensitive food preferences and nutritional deficiency. The objective was to explore the prevalence of those diseases and the dental hygiene among final year high school students as well as to seek any correlation with their eating habits and preferences. Materials and Methods: The study involved 121 students who underwent extraoral and intraoral examination in order to establish the state of the masticatory apparatus whereas the state of oral hygiene was measured as per Silness-Löe plaque index. A questionnaire filled out by the students provided data on the individual characteristics of the masticatory process, eating habits and frequency of consumption of certain cariogenic and anticariogenic foods and beverages. Results: The findings revealed unhealthy food preferences in the target group. The unsatisfactory oral hygiene habits and food preferences account for the high percentage of dental caries. Conclusion: Oral health of children and adolescents is problematic worldwide and can be resolved with the benefits of a balanced diet as well as personal and professional oral hygiene, etc. Teaching children the importance of proper oral care before reaching adolescence can build anticariogenic habits in them for a lifetime.